Andrographolide promotes vincristine-induced SK-NEP-1 tumor cell death via PI3K-AKT-p53 signaling pathway - Zhang M; Xue E; Shao W (Dove Medical Press, 2016)
Mingsheng Zhang, Enda Xue, Wei Shao Department of Pediatric Surgery, Liaocheng People’s Hospital, Liaocheng, Shandong Province, People’s Republic of China Background: Nephroblastoma (Wilms’ tumor [WT]) is the most common malignant renal cancer in children. Although the outcome of WT has significantly improved as a result of the combination of surgery, chemotherapy, and radiotherapy; in some cases WT results in severe complications. Thus, novel strategies that would decrease treatment burden are required. The aim of the current study was to investigate the synergistic antitumor effect of andrographolide (AND) in combination with vincristine (VCR) on WT cells.Methods: Cell Counting Kit-8 assay was used to investigate the synergistic antiproliferation effect of AND and/or VCR on SK-NEP-1 cells in vitro. Meanwhile, SK-NEP-1 xenografts were used to detect the antitumor effect in vivo. Apoptosis and autophagy were then detected by Annexin V, monodansylcadaverine staining. Finally, the underlying signaling transduction was determined with Western blotting.Results: The combination of AND with VCR significantly suppressed SK-NEP-1 cell proliferation in vitro and inhibited xenograft tumor growth in vivo, compared with AND or VCR treatment alone. In addition, the synergistic antitumor effect of AND on the cells was due to an increased apoptosis, not autophagy. Moreover, PI3K-AKT-p53 signaling pathway was involved in the process of combination treatment, which was confirmed when a selective AKT activator was applied.Conclusion: The combination of AND with VCR has a strong synergistic antitumor effect on WT via PI3K-AKT-p53 signaling pathway, thereby representing a potential treatment for WT in the near future. Keywords: andrographolide, vincristine, p53, drug combination